KAJIAN RESPON CALON PENUMPANG ANGKUTAN MASSAL DI KOTA BANDA ACEH - Mufazzil Yusra; Renni Anggraini; Muhammad Isya (JURNAL TEKNIK SIPIL, 2017)
Abstract : Mass Public Transportation System could be an alternative policy in solving the problem of congestion in the city of Banda Aceh. Given the problems such as congestion and uncontrolled number of private transport is supported by the lack of a secondary network that serves as a divider traffic flow or collector (collector) the movement of vehicles began to appear. The government the city of Banda Aceh has provide Bus Rapid Transit (BRT) with the name "Trans Koetaradja" Banda Aceh in order to be a good solution to overcome congestion in Banda Aceh in the long-term policy. The purpose of this research is to know the characteristics of the respondents to the workers and students as users of public transport  the city of Banda Aceh, establish a scenario quality of Service Bus Rapid Transit transport is planned to serve passengers, workers and students examine the response of workers and students as prospective passengers transport provision plan against Bus Rapid Transit, and recommends a form of Bus Rapid Transit service quality that will be provided. The required primary data consist of data characteristics prospective passengers and the data quality of service scenario. The results showed that the results of the analysis to the respondent workers maight certainly go up 10% and 90% is definitely ride and based on the results of the analysis of student respondents might certainly go up 4% and 96% certain ride. Both the respondent's workers and students will definitely switch to using Trans Kutaraja city of Banda Aceh and the respondent's workers and students have the same quality of service factors in choosing the form: cheap rates orders of magnitude , the comfort is good, and a sense of security when I travel by using BRT with BRT schedule the right time.Abstrak: Sistem Angkutan Umum Massal (SAUM) dapat menjadi salah satu alternatif suatu kebijakan dalam menyelesaikan masalah kemacetan di Kota Banda Aceh. Mengingat permasalahan seperti kemacetan dan tidak terkendalinya jumlah angkutan pribadi yang didukung oleh kurangnya jaringan sekunder yang berfungsi sebagai pembagi arus lalu-lintas atau pengumpul (kolektor) pergerakan kendaraan mulai bermunculan. Pemerintah Kota Banda Aceh telah mewacanakan Bus Rapid Transit (BRT) dengan nama “Trans Koetaradja” Kota Banda Aceh agar dapat menjadi solusi dalam mengatasi kemacetan di Kota Banda Aceh dalam kebijakan jangka panjang.  Tujuan penelitian ini adalah untuk mengetahui karakteristik dari responden pekerja dan pelajar selaku pengguna angkutan umum di Kota Banda Aceh, membentuk suatu skenario kualitas pelayanan angkutan Bus Rapid Transit yang direncanakan untuk melayani penumpang pekerja dan pelajar, mengkaji respon pekerja dan pelajar sebagai calon penumpang terhadap rencana penyediaan pelayanan angkutan Bus Rapid Transit, dan merekomendasikan bentuk kualitas pelayanan Bus Rapid Transit yang akan disediakan. Data primer yang diperlukan terdiri dari data karakteristik calon penumpang dan data skenario kualitas pelayanan.  Hasil penelitian menunjukkan bahwa hasil analisa untuk responden pekerja 10% mungkin pasti naik dan 90% pasti naik dan berdasarkan hasil analisa responden pelajar 4 % mungkin pasti naik dan 96% pasti naik. Baik responden pekerja dan pelajar pasti akan beralih menggunakan Bus Trans Kutaraja Kota Banda Aceh dan responden pekerja dan pelajar  memiliki kesamaan dalam memilih faktor  kualitas pelayanan berupa: tingkat besaran tarif yang murah, kenyaman yang baik, dan rasa aman saat melakukan perjalanan dengan menggunakan BRT dengan jadwal BRT yang tepat waktu.